EVALUATION OF ANTIMICROBIAL PROPERTY OF EXTRACT OF PUNICA GRANATUM (L.) ON ORAL PATHOGENS: Pharmaceutical Science-Natural Chemistry - DR.HEMANI K; DR.GHEENA.S (International Journal of Life Science and Pharma Research, 2022)
The aim of the present research was the examination of the potential activity of various organic solvent extracts of Punica granatum on the important microbiota harbouring in the oral cavity. The dried peels and seeds of P. granatum were extracted using chloroform, methanol and nbutanol and their potential activity were studied. The inhibitory effect of crude extracts were observed on various microbial plates which were incubated with different bacterial species in terms of zone of inhibition as mm in diameter. The data was analysed by One Way Analysis of Variance for significance. The peel extract was more potent in inhibiting the microbial population growth as compared to seed extract. While all the four solvents were effective in case of peel extracts, the bioactivity was much higher in species such as Streptococcus mutants, Streptococcus sanguis, Staphylococcus aureus, Lactobacillus acidophilus and Actinomyces viscosus, among 8 species evaluated in the present investigation. The peel extract of P. granatum contains active biomolecule(s) against important oral microbial pathogens and thus holds promise as a potential bioactive molecule against Dental Caries. Based on the bioactivity analysis, the peel extract of P. granatum may further be subjected to purification and characterization of the bioactive compound(s) for regulating oral microbial contamination.